FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENGAJARAN MEMBANGUN MODEL MENTAL BACAAN BAGI GURU SEKOLAH DASAR - Sri Tiatri; Jap Tji Beng; Claudia Fiscarina; Hartinah Dinata (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Building Mental Models Teaching during reading is beneficial to improve students' reading and thinking skills. However, this teaching was not popular because the implementation was complicated. Efforts to develop learning models to build mental models for teachers are continuously being pursued. This study examines the factors that can affect the effectiveness of teacher training. Data is collected through documentation of the entire training process, starting from preparation, implementation, and completion. Interviews and in-depth observations were held in this in-house training process. Participants of this in-house training are a group of primary school teachers in Salatiga (10 teachers) and Tanjungpandan (10 teachers). The results show, there are 5 factors that need to be considered to achieve the effectiveness of in-house training of building mental models: (a) principal support, (b) association with certification, (c) training implementation time, (d) teachers' prior knowledge, (e) teacher habits when teaching in classroom, especially regarding assessment. Based on the evaluation of this training, the material presented was considered quite easy by the teacher. However, there is a tendency that teachers' habits in assessment affect the learning to build mental models that are carried out. There are habits that have the potential to interfere with the freedom of thought that are being developed. Based on the results of this study, it is hoped that the teaching carried out by the teacher can encourage students to think independently, not solely focusing on academic achievement. Pengajaran Membangun Model Mental saat membaca bermanfaat meningkatkan kemampuan membaca dan berpikir siswa. Namun pengajaran ini tidak populer karena pelaksanaannya yang tidak sederhana. Upaya mengembangkan model pembelajaran membangun model mental bagi para guru terus diupayakan. Penelitian ini mengkaji faktor-faktor yang dapat mempengaruhi efektivitas pelatihan guru. Data dikumpulkan melalui dokumentasi seluruh proses pelatihan, mulai dari persiapan, pelaksanaan, dan penyelesaian. Wawancara dan observasi mendalam dilaksanakan dalam proses in house training. Partisipan in house training dalam penelitian ini adalah kelompok guru SD di Salatiga (10 guru) dan Tanjungpandan (10 guru). Hasil penelitian menunjukkan 5 faktor yang perlu dipertimbangkan untuk mencapai keefektifan in house training pembelajaran membangun model mental: (a) dukungan kepala sekolah, (b) pengaitan dengan sertifikasi, (c) waktu pelaksanaan pelatihan, (d) pengetahuan awal para guru, (e) kebiasaan guru dalam pengajaran di kelas, khususnya mengenai penilaian. Berdasarkan evaluasi terhadap pelatihan ini, materi yang disampaikan dianggap cukup mudah oleh guru. Namun ada kecenderungan bahwa kebiasaan guru dalam penilaian mempengaruhi pembelajaran membangun model mental yang dilaksanakan. Ada kebiasaan yang berpotensi mengganggu kemerdekaan berpikir yang sedang dikembangkan. Berdasarkan hasil penelitian ini, diharapkan pengajaran yang dilakukan guru dapat mendorong siswa untuk merdeka berpikir, tidak semata-mata berfokus pada prestasi akademik saja.